(untitled) (Research, Society and Development, 2022)
Objective: to describe the use of Information and Communication Technologies (ICT) among professors of the undergraduate course in Nursing of Federal Education Institutions of Minas Gerais, during the pandemic caused by Covid-19, and to identify the perception of professors in relation to the difficulties faced and perceived facilities in the use of ICTs during that period. Method: a qualitative study, conducted in an online environment with professors from the Undergraduate Nursing Courses at Federal Universities of Minas Gerais. To describe the use of ICTs, a form developed by Rivero and collaborators was used; complemented by guiding questions formulated by the authors. Results: the most used applications for personal communication and with students were e-mail and WhatsApp. The sharing of material additional to that used in the classroom and of work or exercise solutions were the most used features on educational platforms; while the activities with the highest degree of use in teaching were used to support oral exposition and as a communication channel with students. Most teachers consider how to regulate their training on the use of ICT; fully agree with the demand for more time to prepare classes and do not agree that the support of ICT brings the University closer to professional practice. After the incorporation of ICT in the classes, changes were observed in relation to the methodologies. Conclusions: despite the teachers’ prior knowledge of the use of ICT, it was possible to observe obstacles and difficulties in the process of implementing online classes, especially regarding the Nursing course.